Realitas Sosial Dalam Film Miracle In Cell No 7 Kajian Realisme Sosial Georg Lukacs - Della Amadiah; Diera Elika Purba; Rika Maharani; Achmad Yuhdi; Anggia Puteri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to describe the social reality of the film Miracle In Cell No. 7 and relate the social reality of the film Miracle In Cell No. 7 to real life. This research uses qualitative research methods with library study and note taking techniques. The data in this research are transcripts of the film Miracle In Cell No. 7. The results of this research are the social reality of acts of violence, politics and death from the film Miracle In Cell No. 7. There are many incidents that occur. in accordance with social reality, such as in the death executions that occurred in Indonesia but the perpetrator was innocent, then when investigating cases, many police officers resorted to violence to obtain data. In Indonesia, there is a lot of bribery carried out by powerful people for their interests.